Harmonised Approach to the Assessment of Major Accident Risks in the Framework of Seveso II Directive: Case Study on Aramis Methodology Application - Ales Bernatik; Sarka Horehledova; Petra Nevrla (Communications - Scientific letters of the University of Zilina, 2005)
The goal of the contribution is ARAMIS methodology presentation by a specific case study on the assessment of risks of major accidents in an industrial establishment unclassified within the scope of the SEVESO II Directive, but in spite of this the enterprise that represents a significant risk of major accident to employees and neighbouring inhabitants. At present, any legislative pressure is not being produced on the operators of such unclassified sources to make risk analyses and contribute thus to major accident prevention and risk reduction. The ARAMIS methodology was developed as a project within the 5th EC Framework Programme in a team of known European workplaces with the aim to prepare a harmonised methodology for risk assessment especially for the purpose of meeting the conditions of the SEVESO II Directive. A subgoal of the submitted analysis was to test the applicability of the new ARAMIS methodology to the conditions of unclassified risk sources.